Multiple-star wavelength-router network and its protection strategy. - Hill, A.M (IEEE Journal on selected areas in communications)
A wavelength division multiplexed (WDM) multiple-star network and its accompanying path and router protection strategies are proposed for interconnecting N major switch nodes in a national-scale telecommunications network. For a single path failure and uniform traffic matrix, fiber requirements are shown to be less than for a WDM ADM ring, while providing greater resilience to multiple path failures. ?Adding? and ?dropping? only whole wavelength channels between node pairs is found to lead to severe design instabilities and overinvestment in fiber, and time-sharing of wavelength channels is recommended to minimize fiber quantities. A star network capable of interconnecting N=22 switch nodes and an all-optical path protection switching method are verified experimentally, using a 16-channel 2,5-Gbit/s WDM system and a 22×22-port bulk-optics wavelength multiplexer as the hub router. Protection switching speeds within 50 ms are projected for a national-scale network